AD THE ROLE OF RELIGIOUS KURDISH SCHOLARS IN THE RELIGIOUS SCIENCES IN THE KITAB AL-MUNTAZAM BY IBN AL-JAWZI (597AH / 1201 AD): "HISTORICAL-COMMENTARY READING" - Ahmed, Idrees; Ahmad, Khatab (Humanities Journal of University of Zakho, 2025)
The Kurds had an important role in building the Islamic civilization through their participation in various religious sciences such as the sciences of the Qur’an, the sciences of hadith, jurisprudence, Sufism, and other sciences. Reliable historical sources were relied upon, in addition to the book “Al-Muntazam” by Ibn al-Jawzi (597 AH-1201 AD), which is considered the main source for this study. Other sources include the book “Tarikh Baghdad” by Al-Khatib al-Baghdadi (467 AH), “Tarikh Islam al-Dhahabi” (748 AH), and “Al-Bidayah wa al-Nihayah” by Ibn Kathir (774 AH), in addition to other sources and some references. To study the subject in a precise scientific and rigorous manner, it has been divided into thematic axis, which are: the theme on the sciences of the Holy Qur’an, the theme of the Noble Prophetic Hadith, the theme on the jurisprudence, and a theme on other sciences such as Sufis.